New Criteria for Guaranteeing Oscillation of Second-Order Differential Equations with Several Delays (European Journal of Pure and Applied Mathematics, 2025)
The primary objective of this work is to establish new criteria to guarantee the oscillation of solutions for second-order differential equations with p-Laplace type operator. New prerequisites are presented in order to analyze the oscillatory features of the analyzed equation. To support these Öndings, we employed a range of analysis tools, creating new conditions to address some of the problems that have hindered previous research. We were therefore able to obtain results that both build upon and extend those discovered in earlier studies by applying the Riccati transformation and the principles of comparison. Several examples are given to illustrate the significance of our results.
Keywords: Differential equation; oscillation theorems; second-order; delay terms